2, 3, 3′, 4′-Oxydiphthalic dianhydride-based phenylethynyl-terminated imide oligomers for low-temperature resin transfer molding applications. (October 2016) - Meng, Xiangsheng; Zheng, Yan; Yan, Jingling; Li, Yunhui; Wang, Zhen; Li, Guodong
A series of imide resins were prepared using 2, 3, 3′, 4′-oxydiphthalic dianhydride, 4-phenylethynylphthalic anhydride, and aromatic diamines (1, 3-bis(3-aminophenoxy), 3, 4′-oxyaniline, 2, 2′-bis (trifluoromethyl) benzidine, and m -phenylenediamine) as starting materials. These imide oligomers were characterized by means of Fourier transform infrared spectroscopy, differential scanning calorimetry, intrinsic viscosity measurements, and rheological measurements. Some of these oligomers exhibited low (<1 Pa·s at 250°C) and stable (>2 h at 250°C) melt viscosity, which was highly desirable for resin transfer molding process. Thermosetting polyimides (PIs) were then produced from these oligomers via thermal cross-linking reaction of phenylethynyl group. The properties of the thermosets were studied using tensile and flexural testing, dynamic mechanical thermal analysis, and thermogravimetric analysis. The cured PIs exhibited a good combination of thermal and mechanical properties, with a tensile strength of 31–76 MPa, flexural strength of 38–142 MPa, glass transition temperatures of 233–358°C, and 5% weight loss temperatures of 540–545°C under nitrogen atmosphere.